Analisis Pengambilan Keputusan Strategi Bisnis Pada Distro Starcross Di Bandar Lampung Dengan Menggunakan Soft System Methodology - vonny tiara narundana; Satrio Sobri Hamid (Jurnal Manajemen dan Bisnis (JMB), 2021)
Abstract The high competition in the distribution business in the city of Bandar Lampung has an impact on the management of Starcross distributions so that the income received fluctuates every month, this makes researchers aim to find out what alternative strategies are suitable for which Starcross distribution is a priority. for Starcross Distros. in Bandar Lampung. This research uses descriptive analysis method and uses Soft System methodology (SSM) and Annalitical Hierarchy Process (AHP) method. The results of this study indicate that there are three sub-criteria for internal factors and two sub-criteria for external factors. The results of the decision making model using AHP show that the Goal at Starcross Bandar Lampung distribution increases sales with the first priority strategy, namely improving brand image through the Community, Promotion through the Word of Mouth, promotion via the internet and following market trends that consumers are interested in. The alternative strategy for the priority distribution of Starcross in Bandar Lampung is to increase the brand image through the community. Keywords: Business Strategy, Annalitical Hierarchy Process (AHP), Soft System Methodology (SSM)